2019
DOI: 10.1210/js.2019-00078
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome: Pathophysiology, Presentation, and Treatment With Emphasis on Adolescent Girls

Abstract: Polycystic ovary syndrome (PCOS) is a heterogeneous disorder characterized by hyperandrogenism and chronic anovulation. Depending on diagnostic criteria, 6% to 20% of reproductive aged women are affected. Symptoms of PCOS arise during the early pubertal years. Both normal female pubertal development and PCOS are characterized by irregular menstrual cycles, anovulation, and acne. Owing to the complicated interwoven pathophysiology, discerning the inciting causes is challenging. Most available clinical data comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
337
0
31

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(372 citation statements)
references
References 230 publications
(260 reference statements)
4
337
0
31
Order By: Relevance
“…However, some guidelines have recommended that physical activity of longer duration, higher frequency, and intensity result in better maintenance of health. Importantly, moderate to vigorous daily physical activity for at least 60 min is related to better physical and psychosocial health in children and adolescents [66]. Although the low-glycemic diet in PCOS is recommended [46], international guidelines have demonstrated that there is limited evidence as to which specific energy equivalent diet type is better [67].…”
Section: Discussionmentioning
confidence: 99%
“…However, some guidelines have recommended that physical activity of longer duration, higher frequency, and intensity result in better maintenance of health. Importantly, moderate to vigorous daily physical activity for at least 60 min is related to better physical and psychosocial health in children and adolescents [66]. Although the low-glycemic diet in PCOS is recommended [46], international guidelines have demonstrated that there is limited evidence as to which specific energy equivalent diet type is better [67].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, IR, independently from the extent of obesity and magnitude of androgen concentrations, may be present even in lean PCOS. However, transient hyperinsulinemia is typical at puberty and may amplify the individual predisposition to develop PCOS (92).…”
Section: Resolution 2: the Symptoms And Signs Of Pcos Appear Early Inmentioning
confidence: 99%
“…Peripubertal daughters of PCOS women similarly exhibit elevated AMH levels [18,33], in addition to increased circulating LH levels [18], potentially from accelerated hypothalamic gonadotropin-releasing hormone (GnRH) pulsatile release (a trait programmed in rhesus macaques by gestational T exposure or prepubertal androgen excess [34,35]), and increased proclivity for synthesizing the highly biopotent androgen, dihydrotestosterone (DHT) [36], suggesting enhanced androgen action within target tissues. Not surprisingly, therefore, a major goal of pediatric medicine includes identifying girls at risk of PCOS from reliable prepubertal characteristics [37], in order to initiate early preventive therapy and/or treatment [37,38].…”
Section: Pcos and Its Potential Originsmentioning
confidence: 99%